Urban Spatial Patterns of Banda Aceh Using a Shannon Entropy Method - Murtadha*, Amir; Fadhly, Noer; Rusdi, Muhammad (Aceh International Journal of Science and Technology, 2023)
The rapid development of Banda Aceh City has occurred mainly in suburban areas. The impact is that spillover is a complex urban phenomenon that is difficult to measure. Policymakers need a simple method to control and evaluate urban sprawl. This study integrates Shannon's Entropy model with remote sensing and GIS to analyze the pattern of sprawl in each sub-district in Banda Aceh City based on two aspects of distance, namely distance to the city center and road network in order to illustrate the pattern of urban sprawl. The application of Shannon's Entropy method in Banda Aceh City in 2010-2020 can be seen in the Relative Entropy Matrix, which shows that the linear spreading pattern (Quadrant C) is more dominant in Banda Raya Sub-district, Baiturrahman Sub-district, Kuta Raja Sub-district, Kuta Alam Sub-district, Lueng Bata Sub-district, and Syiah Kuala Sub-district. Meanwhile, the transmission pattern of Meuraxa and Jaya Baru sub-districts is in quadrant B, namely the longitudinal type transmission pattern (Radial); in 2020, Jaya Baru sub-district there was a change in the transmission pattern, namely a linear transmission pattern. In the Ulee Kareng sub-district, there is a change in the transmission pattern in 2020, which is in quadrant D, namely the leapfrog development pattern from the previous years, namely 2010 and 2015 in quadrant C with a linear transmission pattern. The spread pattern of Banda Aceh City tends to lead to the East, largely due to landform factors that are very suitable to be used as built-up areas.